East Asian miracle: Economic growth and public policy (Oxford, 1993)
This book examines the public policies of the eight high-performing Asian economies (HPAEs) from 1965 to 1990 that led to faster economic growth than any other part of the world. The countries discussed are Japan, Hong Kong, Indonesia, Malaysia, South Korea, Singapore, Taiwan, and Thailand. Government policies fostered rapid capital accumulation, better schooling for the workforce, increased agricultural productivity, friendly regulatory laws, foreign investment, and targeting of key industries for growth. However, the book concludes that an important lesson for other developing countries is that most countries should not use government interventions in today's changing global economy.
Keywords: East Asia - Economic policy